2006
DOI: 10.1007/s00484-006-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an individualised model of human thermoregulation for predicting responses to cold air

Abstract: Most computer models of human thermoregulation are population based. Here, we individualised the Fiala model [Fiala et al. (2001) Int J Biometeorol 45:143-159] with respect to anthropometrics, body fat, and metabolic rate. The predictions of the adapted multisegmental thermoregulatory model were compared with measured skin temperatures of individuals. Data from two experiments, in which reclining subjects were suddenly exposed to mild to moderate cold environmental conditions, were used to study the effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The humidex formula (Hx) used as a predictor of the preference to decrease temperature (Fig. 8) lacks a theoretical basis, as opposed to the more sophisticated models (Fanger 1972;Gagge et al 1986;Höppe 1993Höppe , 1997Parsons 1993;Givoni 1998;Havenith 2001;Van Marken et al 2007), but it has a long empirical confirmation, namely in Canada (ACSE 2004) and was related to mortality associated with heat waves in Italy (Bisanti et al 2004;Conti et al 2005). The present work showed that the statistical relation between Humidex and the thermal preference votes was clearly stronger than that of the indices based on energy balance of the human body, such as PET or SET*.…”
Section: Discussionmentioning
confidence: 98%
“…The humidex formula (Hx) used as a predictor of the preference to decrease temperature (Fig. 8) lacks a theoretical basis, as opposed to the more sophisticated models (Fanger 1972;Gagge et al 1986;Höppe 1993Höppe , 1997Parsons 1993;Givoni 1998;Havenith 2001;Van Marken et al 2007), but it has a long empirical confirmation, namely in Canada (ACSE 2004) and was related to mortality associated with heat waves in Italy (Bisanti et al 2004;Conti et al 2005). The present work showed that the statistical relation between Humidex and the thermal preference votes was clearly stronger than that of the indices based on energy balance of the human body, such as PET or SET*.…”
Section: Discussionmentioning
confidence: 98%
“…Room temperature has been demonstrated to affect energy expenditure in healthy adults (4547). For accurate resting energy expenditure measurement, attention must be given to ensure steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The models of Stolwijk and Hardy [44] and Stolwijk [46] laid the foundation for several more current physiological models such as Fiala et al [48,392], UC Berkeley [49], Tanabe et al [50], ThermoSEM [51,393] and JOS-2 [394], which use between 15 and 19 segments and hundreds of nodes.…”
mentioning
confidence: 99%